La economía circular en el aprovechamiento de los residuos sólidos orgánicos en las empacadoras de camarón de la provincia de El Oro - Lapo Becerra, Mishelle Del Carmen; Idrovo Peñaranda, Adriana Jamileth (Machala : Universidad Técnica de Machala, 2023)
In the present study, the topic of Circular Economy in the utilization of organic solid waste in shrimp processing plants located in the Province of El Oro is addressed. The primary objective is to analyze how these industries implement this sustainable economic model and manage their organic waste, with a focus on reusing these resources to minimize their environmental impact; this research employs descriptive, correlational, and qualitative approaches, along with interviews as the primary data collection instrument. Findings reveal that many of the shrimp processing plants indirectly apply the principles of the circular economy, suggesting potential for further enhancing sustainability in this crucial industry. The strategic location of these businesses in rural areas of the province stands out as a key factor in optimizing their operations and reducing their environmental footprint. This study provides a comprehensive insight into how the Circular Economy can positively influence the management of organic solid waste in the shrimp processing industry.
En el presente estudio, se aborda el tema de la Economía Circular en el aprovechamiento de los residuos sólidos orgánicos en las empacadoras de camarón ubicadas en la Provincia de El Oro. El objetivo principal es analizar cómo estas industrias implementan este modelo económico sostenible y cómo gestionan sus residuos orgánicos, con un enfoque en la reutilización de estos recursos para minimizar su impacto ambiental: esta investigación utiliza enfoques descriptivos, correlacionales y cualitativos, junto con entrevistas como principal instrumento de recolección de datos. Los hallazgos revelan que muchas de las empacadoras aplican indirectamente los principios de la economía circular, lo que sugiere un potencial para mejorar aún más la sostenibilidad en esta importante industria. La ubicación estratégica de estas empresas en áreas rurales de la provincia se destaca como un factor clave para optimizar sus operaciones y reducir su impacto ambiental. Este estudio proporciona una visión integral de cómo la Economía Circular puede influir positivamente en la gestión de residuos sólidos orgánicos en la industria camaronera.
Keywords: ECONOMIA CIRCULAR; RESIDUOS SOLIDOS ORGANICOS